2015 IEEE International Symposium on Information Theory (ISIT) 2015
DOI: 10.1109/isit.2015.7282422
|View full text |Cite
|
Sign up to set email alerts
|

The likelihood decoder: Error exponents and mismatch

Abstract: Abstract-This paper studies likelihood decoding for channel coding over discrete memoryless channels. It is shown that the likelihood decoder recovers the same random-coding error exponents as the maximum-likelihood decoder for i.i.d. and constantcomposition random codes. The role of mismatch in likelihood decoding is studied, and the notion of the mismatched likelihood decoder capacity is introduced. It is shown, both in the case of random coding and optimized codebooks, that the mismatched likelihood decoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…In the matched setting, an alternative to maximum-likelihood decoding is stochastic likelihood decoding [95], in which each codeword is selected with probability proportional to its likelihood. In [72], ensemble-tight rates and error exponents were studied for a mismatched variant of this decoder in which the likelihood W n (y|x) is replaced by a single-letter decoding metric q n (x, y). These results were further generalized to certain multi-letter metrics in [60], where it was additionally shown that this decoder provides a novel approach to deriving expurgated error exponents.…”
Section: Other Decoding Methodsmentioning
confidence: 99%

Information-Theoretic Foundations of Mismatched Decoding

Scarlett,
Fàbregas,
Somekh-Baruch
et al. 2020
Preprint
Self Cite
“…In the matched setting, an alternative to maximum-likelihood decoding is stochastic likelihood decoding [95], in which each codeword is selected with probability proportional to its likelihood. In [72], ensemble-tight rates and error exponents were studied for a mismatched variant of this decoder in which the likelihood W n (y|x) is replaced by a single-letter decoding metric q n (x, y). These results were further generalized to certain multi-letter metrics in [60], where it was additionally shown that this decoder provides a novel approach to deriving expurgated error exponents.…”
Section: Other Decoding Methodsmentioning
confidence: 99%

Information-Theoretic Foundations of Mismatched Decoding

Scarlett,
Fàbregas,
Somekh-Baruch
et al. 2020
Preprint
Self Cite
“…we have the ordinary likelihood decoder in spirit of [13], [14], [16]. For a(P xy ) = β x∈X y∈YP xy (x, y) ln P (x|y),…”
Section: Notation Conventionsmentioning
confidence: 99%
“…The case of ordinary, deterministic MAP decoding is obtained again as of special case of (5) in the limit β → ∞. As in (13), when the objective function to be minimized over {Q XX ′ Y )}, contains a term like β · G(Q XX ′ Y ) (for some functional G(·)), then in the limit of β → ∞, it is replaced by a constraint of the form G(Q XX ′ Y ) ≤ 0.…”
mentioning
confidence: 99%
“…decoder achieves the optimal random coding exponent when α ∈ [α c , ∞] where α c ∈ [0, 1] depends on the given rate [41][42] [43]. α = 1 corresponds to likelihood decoder and α = ∞ corresponds to the maximum likelihood decoder.…”
Section: A Converse On the Error Exponent Of Weighted Samplingmentioning
confidence: 99%